2007
DOI: 10.1002/macp.200700209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Branch Length on 13C NMR Relaxation Properties in Molten Poly[ethylene‐co‐(α‐olefin)] Model Systems

Abstract: The potential of branch length discrimination for branches containing six and more carbons via bulk NMR relaxation properties in the melt‐state has been explored. A systematic increase in the 13C spin‐lattice relaxation time (T) of the terminal branch carbons 1 and 2 was observed when the branch increased from 6 to 16 carbons in length. The measurement of T via inversion recovery at high‐field showed the most reliable data. The effects of saturation and NOE were addressed by using recycle delays longer than 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…An early study was reported by Hatfield et al using a 200 MHz spectrometer ( 1 H resonance), [34,35] followed by intensive works of Wilhelm, Kaminsky and their co-workers. [33,36,37] Compared (5 of 20) 1600012 to the solution NMR, which has a sample concentration less than 20 wt%, the melt and solid-state 13 C NMR generate a higher sample filling factor, resulting in a higher sensitivity towards the presence of sparsely branched side chains and end groups in POs. This technique currently allows the characterization of branch lengths up to 16 carbons.…”
Section: Ch(b ) Ch(b )mentioning
confidence: 99%
See 3 more Smart Citations
“…An early study was reported by Hatfield et al using a 200 MHz spectrometer ( 1 H resonance), [34,35] followed by intensive works of Wilhelm, Kaminsky and their co-workers. [33,36,37] Compared (5 of 20) 1600012 to the solution NMR, which has a sample concentration less than 20 wt%, the melt and solid-state 13 C NMR generate a higher sample filling factor, resulting in a higher sensitivity towards the presence of sparsely branched side chains and end groups in POs. This technique currently allows the characterization of branch lengths up to 16 carbons.…”
Section: Ch(b ) Ch(b )mentioning
confidence: 99%
“…This technique currently allows the characterization of branch lengths up to 16 carbons. [37] In addition, the measurement acquisition times are greatly reduced. LCBD of 7-8 branches per 100 000 CH 2 groups can be determined by melt-state NMR in 13 h, [36] which represents a vast improvement over the multiday acquisitions required for the solution NMR.…”
Section: Ch(b ) Ch(b )mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the values determined for k bb are composite numbers including the k tr,intra contribution. From a pure technical point of view, extremely high resolutions can be obtained, methods based on 13 C NMR spectroscopy can in principle distinguish between long and short chain branching 90 and thus provide access to separate values for k tr,intra and k bb . ).…”
Section: Chain-end Termination Rate Coefficient (Secondary Radicals)mentioning
confidence: 99%